ANALYSIS OF THE EFFECT OF CAPITAL AND RECEIVABLES ON THE COMPANY'S FINANCIAL PERFORMANCE - Nurfitriani; Eka Yudhyani; Rina Masitho Haryadi; Danna Solihin; Catur Kumala Dewi (Pusat Riset dan Inovasi Nasional, 2022)
The purpose of writing this journal is to determine the existence of working capital, receivables that are focused on the results of financial performance produced based on financial ratios as a calculation tool in cash turnover, accounts receivable turnover, and inventory turnover which determines how much affects the results of financial performance to obtain company profitability so that the company has the finances to obtain company assets with Asset turnover (ROA). This journal research method is carried out using quantitative methods using descriptive research. The population in this analysis is a financial statement to determine the feasibility of financial performance in a company. The research sample is the entire population or what is often referred to as a saturated sample. The method used in collecting this data is to use literature study research and related research results. The results of previous research show that capital and receivables have a significant effect on the financial performance of how a company can manage capital and receivables as a source of company income in carrying out company activities, and financial statements are carried out using financial ratio calculation tools as a form of improvement and if the output in the financial statements can meet the company's obligations to pay the passiva of the company's assets that determine the size and The company's small profitability so that it can be a transparent decision making on the feasibility of financial performance in a company.